Improved Bandwidth of Microstrip Wide-Slot Antenna Using Gielis Curves - Zarifi, Davood; Farahbakhsh, Ali; Mrozowski, Michal (IEEE access, 2024)
The development of a broadband printed wide-slot antenna based on Gielis curves is presented in this article. The printed wide-slot antenna can be conveniently reshaped to achieve ultra-wideband performance by using superformula. The distinct advantage of employing the superformula in design of wide-slot antenna lies in its ability to define nearly any geometric shape including non-standard, complex and non-intuitive for the wide-slot and by finely tuning just six parameters. To demonstrate the capabilities of the proposed approach, a simple prototype is fabricated and tested. The satisfactory correspondence between the measurement and the simulation results confirms the effectiveness of the antenna being proposed. The experimental findings reveal that the antenna's impedance bandwidth, where the VSWR is less than 2, spans from 2 to 13.9 GHz, encompassing a range that is 150% wide. Furthermore, the antenna demonstrates a realized gain ranging between 3.8 to 6.4 dBi within its operational frequency spectrum. These results indicate that the antenna exhibits the efficiency and functionality required for application in wideband communication systems.